Promising ex situ essential oil from Thymus camphoratus (Lamiaceae) - Hrytsyna, M. R.; Kryvtsova, M. V.; Salamon, I.; Skybitska, M. I. (Regulatory Mechanisms in Biosystems, 2020)
The search for new medical fines herbs among species of foreign flora is a relevant issue of today. The article describes the morphological-anatomical, phytochemical peculiarities and antimicrobial action of an endemic species of the Iberian Peninsula Thymus camphoratus Hoffmanns. & Link (Lamiaceae Martinov) introduced to the Botanical Garden of Ivan Franko National University of Lviv. It was determined that the diagnostic peculiarities of medical herbal raw material (herbs) are the structure and woolliness of the stem, leaves and generative organs. Th. camphoratus is a small subshrub with the stele of the stem of bundle type. Leaf lamina is oval, with slightly bent downward, large-crenate margins. Their lower part is woolly with simple crook-like hairs, the upper part is almost bare. The lamina from both sides is densely covered by peltate essential oil-bearing trichomes, between which there are lots of capitate hairs. Peltate trichomes have 4–6 cellular head and are surrounded by 12–16 cells of the epidermis. The epidermis is formed of elongated cells, the stomatal apparatus is of diacytic type, the stromas are densely located on the abaxial side of the leaf. The mesophyll of the leaf is formed of palisade and spongy tissues with no essential oil containing reservoir. The calyx is tubular-campanulate with almost similar short teeth of the upper and lower lip, the corolla has two lips, light-violet, or pink. The perianth is uniformly, woolly externally with single-cellular simple and capitate essential oil-bearing hairs. The inflorescence is compound, raceme-like thyrsoid type. Its opposite, angle partial inflorescences are complex dichasia formed of 7 flower-bearing axes at different stages of development. Determination of qualitative composition of essential oils in the raw material of Th. camphoratus was performed using the method of gas chromatography with gas chromatograph Carlo Erba Vega on capillary columns DB-WAX, 30 m and GC-SCION 456, column SOLGEL-WAX, 60 m with mass spectrometric detector (GCMS) in the Calendula laboratory of the University of Prešov. The standards for the comparison of essential oils were provided by Extrasynthese Ltd. In the raw material, the content of essential oil equaled 0.40 ± 0.05% of air-dried mass, in which 48% was borneol and fenchol, and 20% – linalool and α-terpineol. Essential oil composition of the studied plants is different from the populations in Portugal, where the dominating constituents, except borneol and fenchol, were 1,8-cineol, α-pinene, camphene. The obtained essential oil exerts bactericidal properties against Staphylococcus aureus, Escherichia coli, Streptococcus pyogenes, Enterococcus faecalis and has slightly lower antimicrobial activity towards clinical isolates of these microorganisms. Against single-celled fungi Candida albicans, essential oil from the plants exhibited no inhibition of growth of their colony. According to the results of the conducted studies, it was determined that in the Botanical Garden, Th. camphoratus subsp. congestus was introduced, which due to the content of borneol and fenchol, that have bactericidal effect, can be used as an anti-inflammatory medical preparation.